2020
DOI: 10.37175/stemedicine.v1i2.35
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro neuronal networks for the study of spontaneous activity

Abstract: In the absence of external stimuli, the nervous system exhibits a spontaneous electrical activity whose functions are not fully understood, and that represents the background noise of brain operations. Spontaneous activity has been proven to arise not only in vivo, but in in vitro neuronal networks as well, following some stereotypical patterns that reproduce the time course of development of the mammalian nervous system. This review provides an overview of in vitro models for the study of spontaneous network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…It has been reported that, postnatal day 7 to day 14 is a crucial period for the development of nervous system and the expression of NMDA receptor in rodents ( 21 ). Signaling pathways which contain NMDA receptor have critical functions in learning, memory, cognition, locomotion, and synaptic plasticity ( 22 25 ). Since the administration of NMDA antagonists, including MK-801, during the first three weeks after birth can induce several core symptoms of schizophrenia, these antagonists are widely used in the construction of rodent schizophrenia models ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, postnatal day 7 to day 14 is a crucial period for the development of nervous system and the expression of NMDA receptor in rodents ( 21 ). Signaling pathways which contain NMDA receptor have critical functions in learning, memory, cognition, locomotion, and synaptic plasticity ( 22 25 ). Since the administration of NMDA antagonists, including MK-801, during the first three weeks after birth can induce several core symptoms of schizophrenia, these antagonists are widely used in the construction of rodent schizophrenia models ( 26 ).…”
Section: Discussionmentioning
confidence: 99%